PERBANDINGAN KUAT TEKAN BETON NORMAL DAN BETON DENGAN BAHAN ADDITIVE SILICA FUME ANTARA UJI NON DETRUCTIVE DENGAN UJI DESTRUCTIVE (SUATU PENELITIAN BETON DENGAN FAKTOR AIR SEMEN 0,45 ; 0,50 DAN 0,55) - Muhammad Ali Akoeb (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2011)
Abstract: Purpose of this riset was to determine the value of concrete compressive strength ratio between non-destructive testing of ultra-sonic test method and hammer test with a destructive test is a standard charge of testing. The samples used in the form of a standard cube size 15 cm x 15 cm x 15 cm of 72 specimens consisting of 36 specimens of normal Concrete and 36 specimens for concrete with the addition of silica fume as much as 9% by weight of cement. Tests conducted on the compressive strength of concrete cube specimens with FAS (Factor Air Cement) variation 0.45, 0.50, and 0.55. Specimens tested at ages 7, 14, and 28 days with the three methods of testing. The result showed that the compressive strength of normal concrete in FAS 0.45 for ultra-sonic testing and hammer tests compared with standard tests have an average ratio value β1 (β ultrasonic) of 1.079 and β2 (β Hammer) of 0.555 in fas 0, 50, the average ratio value β1 ((β ultrasonic) obtained at 0.956 and β2 (β Hammer) equal to 0.592. At 0.55 fas obtained an average ratio value β1 (β ultrasonic) of 1.586 and β2 (β Hammer) equal to 0.74.While the strength of concrete with the addition of silica fume on fas 0.45 for ultrasonic testing and Hammer compared with a standard load test has an average ratio value β1 (β ultrasonic) and 1.02 for β2 (β Hammer) equal to 0.726. In fas 0.5 average ratio value β1 (β ultrasonic) obtained at 1.026 and β2 (β Hammer) of 0.690. At 0.55 fas obtained an average ratio value β1 (β ultrasonic) of 1.102 and β2 (β Hammer)B2 of 0.83.Keywords : Ultrasonic Test, Hammer Test, Non Destructive Test, Destructive Test, Compressive Strength of Concrete, Silica Fume.Abstrak: Tujuan penelitian ini adalah untuk mengetahui nilai perbandingan kuat tekan beton antara uji non destructive berupa metode ultrasonic test dan hammer test dengan uji destructive yaitu pengujian pembebanan standar. Benda uji yang digunakan berupa kubus standar ukuran 15 cm x 15 cm x 15 cm, sejumlah 72 buah benda uji yaitu 36 benda uji untuk beton normal dan 36 benda uji untuk beton dengan tambahan silica fume sebanyak 9 % dari berat semen. Pengujian kuat tekan dilakukan terhadap benda uji kubus beton dengan variasi faktor air semen dan umur benda uji. Benda uji kubus beton untuk faktor air semen 0,45 ; 0,50 dan 0,55 diuji pada saat benda uji berumur 7, 14 dan 28 hari dengan ketiga metode pengujian. Dari hasil penelitian diperoleh bahwa kuat tekan beton normal pada FAS 0,45 untuk pengujian ultrasonik dan hammer dibandingkan dengan pengujian pembebanan standar mempunyai nilai perbandingan rata-rata β1 (β ultrasonic) sebesar 1,079 dan β2 (β hammer) sebesar 0,555. Pada FAS 0,50, nilai perbandingan rata-rata β1 (β ultrasonic) yang diperoleh sebesar 0,956 dan β2 (β hammer) sebesar 0,592. Pada FAS 0,55 diperoleh nilai perbandingan rata-rata β1 (β ultrasonic) sebesar 1,586 dan β2 (β hammer) sebesar 0,740. Sedangkan kuat tekan beton additive silica fume pada FAS 0,45 untuk pengujian ultrason